The Implementation of Good Corporate Governance (GCG) in Preventing Fraud at CV. Anugrah Jaya Logistik - Wijaya, Muhammad Aulia; Inayah, Nurul (Jayapangus Press, 2025)
This study aims to analyze the implementation of Good Corporate Governance (GCG) in preventing fraud at CV. Anugrah Jaya Logistik. The research employed a qualitative approach using a case study method. Data were collected through in-depth interviews, observations, and documentation of the company’s internal activities related to the principles of GCG, such as transparency, accountability, responsibility, independence, and fairness.The findings indicate that the implementation of GCG at CV. Anugrah Jaya Logistik is generally well-executed, particularly in the areas of transparency and accountability. However, gaps remain in the aspects of independence and internal supervision, which may create opportunities for fraud. The significant contribution of this study lies in its strategic recommendations for strengthening internal control systems, enhancing employee ethics training, and establishing an independent audit committee to reinforce oversight mechanisms. These findings are expected to serve as a reference for similar companies in implementing GCG more effectively to minimize the risk of fraud in business operations.